Laryngeal extra-skeletal Ewing sarcoma treated with DC-CTL immunotherapy: A case report and review of the literature - Wang, Hanrui; Wang, Jianwei; Wang, Qiang; Yang, Yujuan; Guo, Jing; Ren, Chao; Mou, Yakui; Jia, Chuanliang; Song, Xicheng (Frontiers in Oncology, 2022)
Extra-skeletal Ewing sarcoma (EES) is a rare sarcoma composed primarily of small round cells, capable of metastasizing and relapsing. Few cases of EES originating from the larynx have been reported, and no publications regarding laryngeal EES treated with dendritic cells-cytotoxic T lymphocytes (DC-CTL) immunotherapy have been found. We described a 29-year-old woman with a mass found in the larynx. Diffuse small round cells with scanty cytoplasm shown by histology test and extremely positive staining of CD99 revealed by immunohistochemistry helped determine the diagnosis of laryngeal EES. The patient survived for seven years with no signs of recurrence or metastasis after six cycles of DC-CTL immunotherapy based on traditional treatments. This case indicates that DC-CTL immunotherapy could be considered a new option for treating EES.